"Nguseup" (Proyek Seni Penyadaran; Refleksi Kesadaran Alam dalam Pendekatan Seni Lingkungan) - Hidayatulloh, Taufik Ivan Irwansyah (Journal of Contemporary Indonesian Art, 2022)
"Nguseup" in Indonesian means fishing. Activities usually carried out in rural communities are increasingly becoming a culture that always occurs in every generation. Likewise, what happened to the people of Cibirubeet Village considering the rural geographical conditions that allowed it to happen. The village whose geographical location is flanked by hills and rice fields where all activities are inseparable from the natural life around. So fishing activities are always carried out either to meet food needs or fill the void of mere time. Later there was a problem when some of the rivers flowing in the village no longer produce fish, including the indifference to throwing garbage in some of the river streams. I see this as something that can't be left alone. So direct action by trying to merge with socio-cultural activities in this village is carried out as part of the method of this art project. I assume this "Nguseup" is a conscious art project, hoping that this socio-cultural activity becomes a reflection of the environment with all its life force.